2005
DOI: 10.5194/aab-48-32-2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quality of sperm chromatin structure on in -vitro production of cattle embryos

Abstract: Abstract. Bull effect on results of in vitro embryo production has been well documented. The aim of the present study was to find the relationship between quality of bull sperm chromatin and its effect on in vitro embryo production. Bovine in vitro matured oocytes were fertilized in vitro using capacitated spermatozoa (freshly ejaculated or frozen-thawed) of 12 bulls. Semen was simultaneously processed according to the sperm chromatin structure assay (SCSA) method and was analysed by flow cytometry. At least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 21 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Discussion An attractive feature of IVF is that fewer sexed sperm are needed than for artificial insemination. In our preliminary trials aiming to develop the procedure for capacitation of flow cytometrically sorted sperm (data not shown) it has been found that standard capacitation protocol used in our laboratory for frozen/thawed sperm (KĄTSKA-KSIĄŻKIEWICZ et al, 2005) might be successfully applied for fresh sperm, both sorted and unsorted. However, the sorted and then frozen/thawed fractions of sperm poorly survived after the capacitation treatment and, moreover, only few sperm could be recovered following Percoll's separation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Discussion An attractive feature of IVF is that fewer sexed sperm are needed than for artificial insemination. In our preliminary trials aiming to develop the procedure for capacitation of flow cytometrically sorted sperm (data not shown) it has been found that standard capacitation protocol used in our laboratory for frozen/thawed sperm (KĄTSKA-KSIĄŻKIEWICZ et al, 2005) might be successfully applied for fresh sperm, both sorted and unsorted. However, the sorted and then frozen/thawed fractions of sperm poorly survived after the capacitation treatment and, moreover, only few sperm could be recovered following Percoll's separation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the applied modification limiting preparation of these fractions only to a centrifugation of thawed sperm did not allow removing dead spermatozoa that had been damaged following the cryoconservation procedure, which might exert a detrimental effect on fertilization results. Several authors dealing with in vitro embryo production in cattle (MILLER and HUNTER, 1987;AOYAGI et al, 1988;EYESTONE and FIRST, 1989;GALLI and LAZZARI, 1996;KĄTSKA et al, 1996;CHAMBERLAND et al, 2001;GALLI et al, 2003;KĄTSKA-KSIĄŻKIEWICZ et al, 2005) have described the variability among bulls in the ability of their sperm to become capacitated, fertilize oocytes and subsequently produce competent embryos developing to the blastocyst stage. In terms of factors affecting the outcome of IVF, bull variability has been the main source of difficulty in the work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations